Low‐Temperature‐Processed Colloidal Quantum Dots as Building Blocks for Thermoelectrics - Nugraha, Mohamad I.; Kim, Hyunho; Sun, Bin; Haque, Md Azimul; Arquer, Francisco Pelayo Garcia; Villalva, Diego Rosas; El‐Labban, Abdulrahman; Sargent, Edward H.; Alshareef, Husam N.; Baran, Derya (Advanced energy materials, 2019)
Colloidal quantum dots (CQDs) are demonstrated to be promising materials to realize high‐performance thermoelectrics owing to their low thermal conductivity. The most studied CQD films, however, are using long ligands that require high processing and operation temperature (>400 °C) to achieve optimum thermoelectric performance. Here the thermoelectric properties of CQD films cross‐linked using short ligands that allow strong inter‐QD coupling are reported. Using the ligands, p‐type thermoelectric solids are demonstrated with a high Seebeck coefficient and power factor of 400 μV K−1 and 30 µW m−1 K−2, respectively, leading to maximum ZT of 0.02 at a lower measurement temperature (<400 K) and lower processing temperature (<300 °C). These ligands further reduce the annealing temperature to 175 °C, significantly increasing the Seebeck coefficient of the CQD films to 580 μV K−1. This high Seebeck coefficient with a superior ZT near room temperature compared to previously reported high temperature‐annealed CQD films is ascribed to the smaller grain size, which enables the retainment of quantum confinement and significantly increases the hole effective mass in the films. This study provides a pathway to approach quantum confinement for achieving a high Seebeck coefficient yet strong inter‐QD coupling, which offers a step toward low‐temperature‐processed high‐performance thermoelectric generators. A strategy to enhance electronic coupling using short ligands that allow lower processing temperature and improved thermoelectric performance in p‐type colloidal quantum dots films is studied. The lower processing temperature is found to increase the Seebeck coefficient and reduce the in‐plane thermal conductivity of the films. Fundamental analysis on grain size, carrier density, and effective mass is highlighted to understand these findings.